2017
DOI: 10.18632/oncotarget.16041
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells differentially affect the invasion of distinct glioblastoma cell lines

Abstract: Glioblastoma multiforme are an aggressive form of brain tumors that are characterized by distinct invasion of single glioblastoma cells, which infiltrate the brain parenchyma. This appears to be stimulated by the communication between cancer and stromal cells. Mesenchymal stem cells (MSCs) are part of the glioblastoma microenvironment, and their ‘cross-talk’ with glioblastoma cells is still poorly understood. Here, we examined the effects of bone marrow-derived MSCs on two different established glioblastoma ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(92 citation statements)
references
References 60 publications
8
84
0
Order By: Relevance
“…Thus underlining the importance of accounting for the heterogeneity and phenotypic variations present in actively proliferating tumors. [92] These results emphasize the necessity of considering the use of MSCs from several tissue origins, as well as different types of malignant cells to account for intrinsic in vivo tumor cellular heterogeneity.…”
Section: Importance Of Mscs Tissue Of Origin and Cancer Heterogeneitymentioning
confidence: 88%
See 3 more Smart Citations
“…Thus underlining the importance of accounting for the heterogeneity and phenotypic variations present in actively proliferating tumors. [92] These results emphasize the necessity of considering the use of MSCs from several tissue origins, as well as different types of malignant cells to account for intrinsic in vivo tumor cellular heterogeneity.…”
Section: Importance Of Mscs Tissue Of Origin and Cancer Heterogeneitymentioning
confidence: 88%
“…Tumor heterogeneity may also play a role in cancer‐MSCs interactions and hence influence the conclusions extrapolated from in vitro models. A recent study by Breznik and co‐workers, 2017, demonstrated how phenotypically different cell lines used as models for glyoblastoma can lead to different MSC‐cancer cells interactions and outcomes, with U87 cells showing decreased invasive potential, and U373 cells displaying the opposite, both in vivo and in vitro . The researchers attributed this difference to alternatively favored metabolic pathways resulting from TGF‐β release by MSCs.…”
Section: Cancer‐mscs Co‐culture Relevance In 3d In Vitro Tumor Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The embryonic mesenchyme, or embryonic connective tissue or undifferentiated mesenchyme, is made up of star-shaped branched cells with a high mitotic rate (high reproductive capacity); they are considered as pluripotent cells because they can differentiate into several different tissues [28,29,30]. …”
Section: Origin Of the Collagens/connective Tissuementioning
confidence: 99%